METODE MAPAN Menggagas Metode Baru Menulis Huruf Arab Lebih Singkat - Dayudin Subangkit; Ateng Rohendi (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2019)
One aspect of learning Arabic is writing Arabic. The ability to write Arabic is supported by the ability to write letters properly and correctly. The better writing of Arabic letters will have an impact on the quality, accuracy and beauty of Arabic writing. The ability to write Arabic letters among Islamic students, even students majoring in Arabic, are on average low and do not meet the standards. This has an impact on the weak and good ability of Arabic. Research on early semester at the Arabic Language and Literature Department of the Faculty of Adab and Humanities at UIN Sunan Gunung Djati Bandung showed that students were still having difficulty writing Arabic letters properly. The difficulty is due to the following factors: First, the unfamiliarity of students writing sentences in Arabic. Second, the unfamiliarity of writing from the right side with the peculiarities of Arabic letters that require their own expertise. Third, weak Arabic language ability requirements and Arabic writing tests in the entrance test for admissions to Arabic majors. This study initiated a new method of writing Arabic letters more effectively through the anatomical approach of letters to facilitate the learning of Arabic writing. This new method is named Metode Mapan which dissects anatomically the structure of Arabic letters by separating the letters based on loose letters, connecting letters, variations in letters, punctuation marks, and numbers to create ease of Arabic writing so that more effective, easier, methodologically correct and aesthetically beautiful. The psychological impact of the findings of this study is expected to lead to a penchant for Arabic writing which has been considered difficult.